«ҲАЎА БАСЫМЫ» ТЕМАСЫНА БАЙЛАНЫСЛЫ ӘМЕЛИЙ МӘСЕЛЕЛЕРДИ ШЕШИЎ УСЫЛЫ - Утепбергенов, Ж. (FAN va JAMIYAT, 2016)
The article deals with the methods of developmentof learners‘ mathematic competency through the solution of practical tasks at the lessons in Geography.